Roles of TGF-beta and periostin in fibrosclerosis in patients with IgG4-related diseases. (December 2013) - Ohta, Nobuo; Kurakami, Kazuya; Ishida, Akihiro; Furukawa, Takatoshi; Suzuki, Yusuke; Aoyagi, Masaru; Matsubara, Atsushi; Izuhara, Kenji; Kakehata, Seiji
Abstract Conclusion: These results suggest that transforming growth factor (TGF)-beta and periostin could be useful as novel biomarkers and therapeutic targets in IgG4-related disease. Objectives:IgG4-related disease is an uncommon fibrosclerosing and inflammatory mass-forming disease that can be systemic or can affect single organs. To clarify the roles of TGF-beta, periostin, and interleukin (IL)-13 in the pathogenesis of IgG4-related disease, we studied a total of 36 serum and 11 tissue samples from patients with IgG4-related disease. Methods: This was a retrospective clinical study. The patient group consisted of six females and seven males (average age 60 years, range 38–74 years). Serum IgG4 levels, the tissue density of IgG4-positive plasmacytes, and the expression of TGF-beta and periostin in the affected tissues were examined immunohistochemically. Results: Serum IgG4 levels were elevated in all patients (mean 776.6, range 185–2820 mg/dl), and IgG4-positive plasmacytes were observed in the affected salivary glands. Seven patients with prominent infiltration of the involved glands with IgG4-positive plasmacytes had fatal systemic complications, including pancreatitis, after swelling of the salivary glands. Overexpression of TGF-beta and periostin was observed in affected tissues obtained from these patients.